Panel data analysis on the impact of corporate governance on firm performance: evidence from Bursa Malaysia companies with good CG disclosures / Tun Yin Li ... [et al.] - Tun, Yin Li; Low, Suet Ching; Shanmugaretnam, Shubatra; Teh, Beverly Boon Gaik (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2024)
Using Panel Data Analysis, this research investigated the performance of the firm from the top 100 companies with good CG disclosures (2019) on Bursa Malaysia against corporate governance mechanisms. The study period was 2013 – 2019. Firm performance was measured using Earnings per share (EPS), Tobin Q (TQ) and Return on Equity (ROE) while corporate governance mechanisms were CEO Duality (CDUAL), Board Size (BSIZE), Independent Directors BIND), Board Meetings (BMEET), Women Directors (WOMD), Foreign Qualifications’ Directors (FORD). Little evidence was recorded for the period under the study. CDUAL was only significant with ROE, BSIZE was significant with EPS & ROE, BIND was significant with TQ & ROE, BMEET significant with TQ & ROE. OMD significant with TQ & ROE, FORD was only significant with EPS. Results indicated the companies with good CG disclosures do not correspond with firm performance. Much more CG compliance needs to be done to improve firm performance.